(untitled) (Revista Brasileira Multidisciplinar, 2010)
The main objective of this paper has been to identify and to analyze the social and historical context that led to the drafting of the Learning Law, becoming part of a dissertation presented to the Post-Graduate Master of Regional Development and Environment of Centro Universitário de Araraquara-UNIARA. A literature search allowed us to understand the significance of childhood, adolescence and work, and it has also been demonstrated that in Brazil, child labor has always been and is still directly linked to the socioeconomic condition of the concerned individual’s family. As a consequence, the law, that was issued on the basis of public policy, aiming at opening opportunities for adolescents who are born into poor families, if not applied properly, has its scope limited in order to become an instrument of legitimizing the ideology that considers early work normal and encourages the maintenance and reproduction of the current domination.